Places of safety? Fear and violence in acute mental health facilities: A large qualitative study of staff and service user perspectives - Jenkin, Gabrielle; Quigg, Stewart; Paap, Hannah; Cooney, Emily; Peterson, Debbie; Every-Palmer, Susanna (PLOS ONE, 2022)
Aim To understand violence on acute mental health units according to staff and service user perspectives and experiences. Background The collateral damage of violence in acute inpatient mental health settings is wide-ranging, impacting on the health and wellbeing of staff and service users, and detrimental to public perceptions of people who are mentally unwell. Despite international research on the topic, few studies have examined psychiatric unit violence from both staff and service user perspectives. Methods We conducted in-depth interviews with 85 people (42 staff, 43 service users) in four adult acute mental health inpatient units in New Zealand. We undertook a thematic analysis of perspectives on the contributing factors and consequences of violence on the unit. Results Both staff and service users indicated violence was a frequent problem in acute inpatient units. Four themes regarding the causes of violence emerged: individual service user factors, the built environment, organisational factors, and the overall social milieu of the unit. Staff often highlighted complexities of the system as causal factors. These included the difficulties of managing diverse service user illnesses within an inadequate and unsafe built environment whilst having to contend with staffing issues and idiosyncrasies relating to rule enforcement. In contrast, service users talked of their needs for care and autonomy not being met in an atmosphere of paternalism, boredom due to restrictions and lack of meaningful activities, enforced medication, and physical confinement as precipitants to violence. Two broader themes also emerged, both relating to empathy. Both staff and service users exhibited ‘othering’ (characterised by a profound lack of empathy) in relation to acutely unwell individuals. Explanations for violent behaviour on the unit differed between groups, with service users being more likely to attribute unwanted behaviour to contextual factors and staff more likely to ‘blame’ mental illness. The consequences of violence included stress, physical injury, and a culture of fear and stigma. Conclusion Violence in acute inpatient mental health units in New Zealand is a significant, complex, and unresolved problem negatively impacting the therapeutic mission of these settings. Further in-depth qualitative investigations are urgently required into what is experienced as violence by service users, their view of how violence occurs, the role of fear and power relations, and the contributions of the built and organisational environment to all forms of violence to all unit users. A core function of the acute mental health unit is to offer a therapeutic environment for individuals at their most vulnerable. For this to happen, the unit must be a rewarding place to work, and a safe place to be.